Freezing and thawing technique for the removal of suspended solids and concentration of palm oil mill effluent (POME) - Yee, Phang Lai; Wakisaka, Minato; Shirai, Yoshihito; Hassan, Mohd. Ali (Informa UK Limited, 2002)
More than 70% of the SS removal from POME was achieved at the thawing rate less than 5 ml/min from 200 g of the frozen POME. However, the efficiency of the SS removal deteriorated at a higher thawing rate (7.1-13.6 ml/min). In addition to SS removal, concentration changes of thawed solution occurred at a lower thawing rate. At thawing rates from 1.7 ml/min to 4.2 ml/min, the melted solution was concentrated 1.2-1.3 times and 1.2-1.4 times respectively according to the COD soluble index and electrical conductivity index. Thus, the thawing rate played an important role in the freezing and thawing of POME for the purposes of SS removal and concentrating the effluent.